Status of Novel Cardiovascular Risk Factor and Cardiovascular Disease Risk in an Urban Cuban PopulationA Pilot Study - Rodriguez-Ojea, Arturo; Alonso, Celia; Yarnell, John WG; Woodside, Jayne V (Journal of Health, Population and Nutrition, 2011)
Cardiovascular disease is the main cause of death in Cuba, yet the prevalence of novel risk factors is not known. To examine the prevalence of risk factors of traditional and novel cardiovascular diseases (CVDs) among an urban Cuban population, a cross-sectional pilot survey was undertaken in Havana city, Cuba. Ninety-seven adults aged 45-60 years registered to receive medical care at a policlinic. The prevalences of rates of CVD risk factors were: hypertension (≥140/90 mmHg) (53.6%), hypercholesterolaemia (total cholesterol >5.2 mmol/L) (47.0%), low high-density lipoprotein (HDL)-cholesterol (<1.03 mmol/L) (64.3%); diabetes (self-reported) (24.6%); metabolic syndrome (ATP III criteria) (58.2%); overweight and obesity (body mass index ≥25 kg/m2) (78.0%); current smoking (39.3%); elevated level of C-reactive protein (3 <value <10 mg/L) (32.1%), low lipid-standardized vitamin E levels (<5 μmol/mmol of total cholesterol) (69.6%); and high tHcy levels (>15 μmol/L) (11.1%). The total carotenoid status was independently associated with waist-circumference and risk of diabetes and metabolic syndrome. In this small unrepresentative sample of people aged 40-65 years from Havana city, there was a high prevalence of traditional and novel CVD risk factors. The total serum carotenoid status appeared to be associated with an increased prevalence of CVD risk factors. Key words: Cardiovascular diseases; Carotenoids; Cross-sectional studies; Obesity; Risk factors; Cuba DOI: http://dx.doi.org/10.3329/jhpn.v29i5.8905 JHPN 2011; 29(5): 510-515